ANALISIS PENGAMBILAN KEPUTUSAN UNTUK PEMBELIAN MAKANAN KEMASAN BERLOGO HALAL MUI (STUDI KASUS IBU RUMAH TANGGA DI PERUMAHAN AUR DURI DAN PERUMNAS KOTA BARU, KOTA JAMBI) - Lavlinesia; Hana Jusia, Putri; Murdi, Saad (JALOW | Journal of Agribusiness and Local Wisdom, 2020)
Food is a basic need that must be available all the time for human survival. Food as a source of energy must be of high quality. In 2016, the Indonesia Ministry of Health issued a program on the consumption of nutrition and safety food. Indonesia is the country with the most Muslim population in the world with 87.17 % of the total Indonesian population of 255,461,700 people (BPS, 2015). It is well known that to get proper food by an individual is consider as ones’ right that must be satisfy. Therefore, food as a strategic commodity perceive to satisfy the right of an individual to obtain a proper consumption of food. Halal food does not only cover religious aspects. Halal certified products have gone through the production process which takes quality, processing, and cleanliness of a product into account. The demand for halal food products is increasing and has been widely proven on the market implementation. Not only in Muslim-majority countries but in developed countries which do have high living standards including standards for quality assurance of food products. The respondents of the study are household wives reside in Aur Duri Residential and Kota Baru Residential, Jambi. The study collected 96 respondents who filled up the surveys. Moreover, the study signified that there are 43 (44 %) respondents who prefer the MUI Halal logo affect their purchase intention. It is influenced by characteristics in terms of religion, age and education. Knowledge, compliance based on beliefs, and awareness of quality assurance and food security affects the perceptions of household wives to the decision to purchase food with halal logo MUI packaging. The marketing strategy that most influences the purchase intention on an individual are price and products that become daily necessities.